2007
DOI: 10.1016/j.brainres.2007.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid mediated plasticity in exocytosis observed in PC12 cells

Abstract: Membrane composition serves to identify intracellular compartments, signal cell death, as well as to alter a cell's electrical and physical properties. Here we use amperometry to show that supplementation with the phospholipids phosphatidylcholine (PC), phosphatidylethanolamine (PE), sphingomyelin (SM), and phosphatidylserine (PS) can alter several aspects of exocytosis. Changes in the amperometric peak shape derived from individual exocytosing vesicles reveal that PC slows expulsion of neurotransmitter while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
83
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 39 publications
11
83
0
Order By: Relevance
“…An important goal for future research is to design experiments that can distinguish between various alternative mechanisms by which PS can influence exocytosis. Many proteins regulate fusion pores ), but we know less about the effects of lipids (Uchiyama et al, 2007;Lam et al, 2008). In comparison with proteins, lipids are difficult to manipulate in living cells, due to the complex regulation of lipid-metabolizing enzymes (Vance and Vance, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important goal for future research is to design experiments that can distinguish between various alternative mechanisms by which PS can influence exocytosis. Many proteins regulate fusion pores ), but we know less about the effects of lipids (Uchiyama et al, 2007;Lam et al, 2008). In comparison with proteins, lipids are difficult to manipulate in living cells, due to the complex regulation of lipid-metabolizing enzymes (Vance and Vance, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…As an initial attempt to test the role of PS in exocytosis, we added 100 M PS directly to the culture medium (Uchiyama et al, 2007). Two days later, lipid analysis with HPLC showed that this raised the total PS content of PC12 cells from 10.3 to 12.1% (Table 1).…”
Section: Ps Effects On Exocytosismentioning
confidence: 99%
“…The most direct evidence that the fraction released can be altered was presented by both the Amatore and Ewing groups who showed that the amount of neurotransmitter released per event can be quickly altered by influencing the lipid composition of the plasma membrane (Amatore et al 2006;Mellander et al 2012;Uchiyama et al 2007). In one case, they found that a shortterm incubation of PC12 cells with the inverted cone shaped lipid lysophosphatidylcholine (LPC) increased the average amount of dopamine released per exocytosis event while incubation with the cone shaped phosphatidylethanolamine (PE) decreased it.…”
Section: Lipid Composition Of the Plasma Membranementioning
confidence: 99%
“…Amatore et al recently showed that these lipids could each produce the opposite effect when added to the extracellular media (the noncontact side of the fusing membranes) of chromaffin cells undergoing exocytosis (33). In a similar experiment PC12 cells were incubated with dipalmitoylphosphatidylcholine, a lamellar lipid (close to no intrinsic curvature), resulting in a decrease in the rate of exocytosis (34). In summary, experiments with model systems show that physical manipulation can be used to redistribute membrane composition, and cell experiments show that altering composition can regulate the dynamics of the fusion event.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that function and structure dictate membrane composition rather than a mechanism where composition is altered in anticipation of function. This membrane composition is clearly important in determining cellular regulating factors, and recent observations have shown that incubation with lipids can alter the rate of chemical release via exocytosis (34,35). If, indeed, structure dictates the chemical composition of membranes, then it is convenient to speculate that membrane fusion events during exocytosis result in a subsequent change in local membrane composition.…”
Section: Discussionmentioning
confidence: 99%